Linguistic Policy in Switzerland: the Paradigm Shifts but the Complexity Remains - Nicolas Schmitt (Revista de Llengua i Dret - Journal of Language and Law, 2017)
Taking into account the history and experiences of multilingual and multicultural Switzerland, this article pursues two goals. Firstly, to demonstrate that the official recognition of several languages is proof of wisdom, and an important factor in preserving peace and stability, because it is a sign of respect towards minority languages and communities. Secondly, as a reminder that this static dimension has to be accompanied by a strong political will, favourable pre-conditions, and a subtle political sense of adaptation to new circumstances (the dynamic dimension), like the defence of endangered minority languages. This paradigm shift has been enshrined in the Swiss Constitution since as early as 1996 and represents a certain infringement on the federal structure of the country. But linguistic policy is a never-ending story, and authorities should always be ready to integrate new developments in the linguistic Constitution, like the overwhelming and sometimes undesirable supremacy of English.